THE DYNAMICS MEANING OF TORTOR DANCE IN THE CONTEMPORARY AGE: AN ANALYSIS OF MEANING CHANGES IN THE PERSPECTIVE OF SYMBOLIC INTERACTION HERBERT BLUMMER - BIJAK GINTING (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The tortor dance has an important role in every Batak traditional event, but it can be clearly seen that there are many Toba Batak people who do not understand the meaning of each tortor dance movement at the time of the wedding ceremony. In this study, we will try to see this with Hebert Blumer's theory of symbolic interaction. This research is a reflective qualitative research with a library study approach. The data are taken from various sources such as books, journals, and others. The results showed that most of the Toba Batak people did not know what the meaning of the tortor dance was in the Toba Batak marriage ceremony. The wedding ceremony does not use accompaniment music in the form of gondang, but the accompaniment music is replaced with keyboard music, for reasons that are more practical and modern. The current shift for women's clothing has been to wear the kebaya and ulos wrapped around the outside of the clothes. Based on the results of the study, many people who became panortors at traditional wedding events left the culture of wearing ulos as one of the devices in the manortor that should be used, and it is not uncommon to find many panortors or female dancers who do not wear gloves or only wear pants when will join the manortor thereby reducing the value of politeness